Mycobacterium tuberculosis complex detected by modified fluorescent in situ hybridization in lymph nodes of clinical samples - Juan Rodriguez-Nuñez; Francisco J Avelar; Francisco Marquez; Bruno Rivas-Santiago; Cesar Quiñones; Alma L. Guerrero-Barrera (Journal of Infection in Developing Countries)
Introduction:  Lymph node tuberculosis (TB) is the leading cause of extrapulmonary tuberculosis and is the most frequently identified type in Aguascalientes, Mexico. Conventional diagnosis has serious limitations for rapid detection of extrapulmonary tuberculosis in clinical samples. Here PCR and modified FISH have been tested as complementary diagnosis methods for extrapulmonary tuberculosis. Methodology: The specific insertion sequence IS6110 for Mycobacterium tuberculosis complex was used to perform PCR and build DNA and PNA FISH probes (20bp). PCR and modified DNA and PNA FISH assays were performed to evaluate 41 lymph node paraffin-embedded tissue samples, in comparison with the histopathology diagnosis, which was considered the gold standard (22 positive and 19 negative). Results: In comparison with histopathology diagnosis PCR showed 62.5 % sensitivity and 77.8 % specificity (χ2 = 4.583 p < 0.05). Modified DNA FISH showed 71.4% sensitivity and 84.6% specificity (χ2 = 11.21 p < 0.05). PNA FISH showed 66.7% sensitivity and 60.0% specificity (χ2 = 2.93 p > 0.05). Ziehl Neelsen stain was positive in only four cases of 22 lymph node samples positive to histopathology.  In contrast, PCR and modified DNA FISH were positive in 20 cases of the same group. The negative cases were coincident in all tests. Conclusions: PCR and DNA FISH showed a significant increase in the number of cases detected and also showed higher sensitivity and specificity compared with data reported by traditional methodology. In developing countries, these techniques could help to complement the early diagnosis and timely treatment of extrapulmonary tuberculosis.